Community Service Workshop on Designing a Deep Learning Model to Strengthen Inclusive and Moderate Religious Education - Effendi, Muhamad Ridwan; Narulita, Sari; Barnansyah, Rudi Muhammad; Nastiar, Muh Fauzan; Salsabila, Ma'wah; Sanusi, Sobar; Oktovia, Irma (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Deep learning is a model of development from Merdeka Belajar Curriculum that focuses on students' deep understanding and critical thinking, not just memorisation. The three main components are Mindful Learning, Meaningful Learning, and Joyful Learning. However, many educators, including Islamic Religious Education teachers, still experience difficulties implementing it due to a lack of training. This service activity introduces the deep learning approach to PAI teachers in PGRI and AGPAII Bojong District, Purwakarta. The methods used include interactive training and case studies to provide practical understanding. The results of this activity are training modules and practice guides that can be applied in schools. The evaluation showed that 57.1% of participants had never attended a similar workshop, 78.6% planned to implement it in their learning, and 100% recommended repeating this activity. Thus, this activity has a positive impact, changing the understanding of PAI teachers and increasing good practices in deep learning in the community.